NNS tridentate thiosemicarbazide and 1, 3, 4-thiadiazole-2-amine complexes of some transition metal ions: syntheses, structure and fluorescence properties. Issue 7 (2nd April 2016) - Bharti, A.; Bharati, Pooja; Singh, N.K.; Bharty, M.K.
Abstract: The reactions of Zn(II), Mn(II), and Ni(II) acetates with 1-picolinoyl-4-phenyl-3-thiosemicarbazide (Hppts) yielded [Zn(ppts)2 ]·CHCl3 (3 ), [Mn(ppts)2 ]·THF (4 ), and [Ni(ppts)2 ]·THF (5 ), respectively, but HgCl2 gave a cyclized product N-phenyl-5-(pyridin-2-yl)-1, 3, 4-oxadiazole-2-yl-amine (2 ). The treatment of Hppts with conc. H2 SO4 formed N-phenyl-5-(pyridin-2-yl)-1, 3, 4-thiadiazole-2-yl-amine (1 ). Hppts is a nonfluorescent material, but3, 4 and the cyclized products 1, 3, 4-oxadiazole/1, 3, 4-thiadiazole are fluorescent. The cyclized ligand N-phenyl-5-(pyridin-2-yl)-1, 3, 4-thiadiazole-2-amine (1 ) formed [Zn(2-Hppt)2 (OAc)2 ] (6 ) and [Cd2 (2-Hppt)2 (OAc)2 ( μ -OAc)2 ] (7 ) in which Cd(II) has a binuclear acetate-bridged seven coordinate pentagonal bipyramidal geometry. Complex7 is also a fluorescent material with maximum emission at 425 nm at an excitation wavelength of 254 nm. Abstract :